SAFETY AND SECURITY IN SPACE TRAFFIC MANAGEMENT REGULATIONS - POLKOWSKA Małgorzata (2018)
The Space Traffic Management (STM) is a new concept referring to the space activities. The highest priority is safety and security of outer space and all conducted operations. There is no definition of STM. There is an urgent need to regulate STM providing safety and security regulations at international, regional and national level. Due to the fact that there is no STM definition, the regulator might use the example of existing regulations of International Civil Aviation Organization on Air Traffic Management (ATM). There are many questions, still open, regarding specific regulations needed and at which level they should be made: globally or nationally.